The impact of economic news on bond prices: Evidence from the MTS platform - Paiardini, Paola (Journal of Banking & Finance, 2014)
Although there is an extensive literature on the impact of macroeconomic announcements on asset prices, the bond market has received less attention than the foreign exchange and equity markets, even less if we consider the European market. This paper uses high-frequency intra-day data over a three-year period to investigate the impact of regularly scheduled macroeconomic news and monetary policy announcements on the returns of the Italian government bond market, the largest one in the Euro-zone. With respect to the previous papers, we use a much broader set of announcements, 68, and a relatively novel dataset (MTS). We find that 25 news have a significant impact on bond returns and that almost all announcements are incorporated into prices within 20min from the release.